Identification of psychosocial factors of noncompliance in hypertensive patients - Hassan, Norul Badriah; Che Ismail, Hasanah; Foong, K.; Naing, Lin; Awang, R.; Ismail, Shaiful Bahari; Ishak, A.; Yaacob, Lili Husniati; Mohd Yusoff, Harmy; Daud, Adibah Hanim; Shaharom, Mohamed Hatta; Conroy, R.; et al. (Nature Publishing Group, 2006)
This cross-sectional study was aimed to identify the predictors of medication noncompliance in hypertensive patients. The study was conducted at the Family Medicine Clinic, Hospital Universiti Sains Malaysia, Kelantan, Malaysia, which is a university-based teaching hospital. All hypertensive patients aged 40 or over-registered from January to June 2004, who had been on treatment for at least 3 months, were screened. Previously validated self-administered questionnaires were used to assess the compliance and psychosocial factors. A total of 240 hypertensive patients were recruited in the study. Of these, 55.8% were noncompliant to medication. Logistic regression showed that age (adjusted odds ratio (OR): 0.96; 95% confidence interval (CI): 0.92–0.997; P: 0.035), patient satisfaction (adjusted OR: 0.97; 95% CI: 0.93–0.998; P: 0.036) and medication barrier (adjusted OR: 0.95; 95% CI: 0.91–0.987; P: 0.009) were significant predictors of medication noncompliance. Therefore, younger age, poor patient satisfaction and medication barrier were identified as independent psychosocial predictors of medication noncompliant in hypertensive patients.